2000
DOI: 10.1007/s003470070035
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividueller Vergleich von Intraokularlinsen aus hochrefraktivem Silikon (Allergan SI40NB) und hydrophobem Acrylat (Alcon Acrysof MA60BM)

Abstract: One year after implantation of foldable, highly refractive silicone and hydrophobic acrylic IOLs using a self-sealing tunnel incision and phacoemulsification, no significant functional or morphological differences between the two IOL types were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…Other studies do not show any association between glistenings and decreased visual function; Allers et al. (Allers et al. 2000) made an intrapatient comparison between the same hydrophobic acrylic (AcrySof MA60BM) and silicone [SI40NB; Abbott Medical Optics (previously Allergan)] IOLs as in our study and found no statistically significant difference in visual acuity between the IOL groups, although lens glistenings were present in 40% of the AcrySof IOLs.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Other studies do not show any association between glistenings and decreased visual function; Allers et al. (Allers et al. 2000) made an intrapatient comparison between the same hydrophobic acrylic (AcrySof MA60BM) and silicone [SI40NB; Abbott Medical Optics (previously Allergan)] IOLs as in our study and found no statistically significant difference in visual acuity between the IOL groups, although lens glistenings were present in 40% of the AcrySof IOLs.…”
Section: Discussionsupporting
confidence: 48%
“…The effect of lens glistenings on postoperative visual function remains controversial (Dhaliwal et al. 1996; Allers et al. 2000; Miyata et al.…”
Section: Introductionmentioning
confidence: 99%
“…They seem to reduce the contrast sensitivity [ 11 , 13 ]. However, in contrast to calcifications, a reduction of visual acuity is rare [ 11 , 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Das morphologische Korrelat sind Vakuolen innerhalb des Linsenmaterials. "Glistenings" scheinen zwar das Kontrastsehen verschlechtern zu können [3,9], aber im Gegensatz zu Kalzifikationen ist eine signifikante Visusminderung eher selten [1,3,9]. …”
Section: Introductionunclassified